2018
DOI: 10.1111/ejn.14209
|View full text |Cite
|
Sign up to set email alerts
|

Waist‐to‐hip ratio affects female body attractiveness and modulates early brain responses

Abstract: This investigation examined the electrophysiological response underlying the visual processing of waist-to-hip ratio (WHR) in female bodies, a characteristic known to affect perceived attractiveness. WHRs of female bodies were artificially adjusted to values of 0.6, 0.7, 0.8 or 0.9. Behavioural ratings of attractiveness of the bodies revealed a preference for WHRs of 0.7 in the overall group of participants, which included both male and female heterosexual individuals. Event-related potentials (ERPs) were then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 67 publications
(120 reference statements)
0
3
0
Order By: Relevance
“…In this special issue, Del Zotto et al. (2018) examined the perceived attractiveness of a secondary sexual characteristic of the human body—waist‐to‐hip ratio, in a behavioural task and in an EEG paradigm. They also aimed to test the role of attention and top‐down mechanisms by asking the participants to selectively attend to the body stimuli versus not in the ERP task.…”
Section: Body Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…In this special issue, Del Zotto et al. (2018) examined the perceived attractiveness of a secondary sexual characteristic of the human body—waist‐to‐hip ratio, in a behavioural task and in an EEG paradigm. They also aimed to test the role of attention and top‐down mechanisms by asking the participants to selectively attend to the body stimuli versus not in the ERP task.…”
Section: Body Processingmentioning
confidence: 99%
“…The final paper of this group used behavioural ratings to determine which waist‐to‐hip ratio was the most attractive, and they showcased how the early P1 and N1 components are modulated by attention and waist‐to‐hip ratio (Del Zotto et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, Singh [ 17 ] found that WHR was the key variable associated with attractiveness in women, both in terms of personality characteristics and physical attractiveness. Research indicates that an optimal WHR is closer to 0.7 [ 18 ].…”
Section: Introductionmentioning
confidence: 99%